Anti-inflammatory Effect of AMPK Activators from Natural Products in RAW 264.7 Cell Model (P06-095-19). (13th June 2019) - Yang, Hong; Zhao, Lingling; Stevenson, Douglas; Bartlett, Mark; Lou, Bin
Abstract: Objectives: AMP-activated protein kinase (AMPK) is a serine/threonine protein kinase critically involved in the regulation of cellular energy homeostasis. Many studies have suggested that AMPK activation exert significant anti-inflammatory effects. In this study, we assessed the anti-inflammatory effect of AMPK activator from natural products, Broccoli seed (BS, Brassica oleracea var. italic) extract and Sweet tea (ST, Rubus Suavissmu s S. Lee) extract, in RAW264.7 cells. Methods: AMPK assay Natural product samples treated purified AMPK enzyme (CycLex Co., Ltd. Japan) or cell lysates were added to the well of CycLex AMPK kinase assay kit, then performed. Cell Culture HepG2 and RAW264.7 cells were cultured in Dulbecco's Modified Eagle Medium supplemented with buffer. ELISA assay of IL-6 RAW264.7 cells were incubated with LPS, with or without presence of natural products, IL-6 in the supernatant was determined with Mouse IL-6 ELISA Kit . Western Blotting Cells were treated with LPS in the presence of or absence of natural products for 6 h, then lysed with buffer and a protease inhibitor. Proteins separated and blotted onto PVDF, blocked and probed with antibodies against caspase-1, finally incubated with the goat anti-rabbit horseradish-peroxidase coupled secondary antibody. The target proteins were analyzed using the ChemiDoc XRS System and quantified by ImageJ. Results: Natural products BS and ST were identified as AMPK activators with the established AMPK activity assay model. (Fig. 1) Macrophages were stimulated with LPS, while the secretion of IL-6 was decreased in the presence of BS or ST, the protective effect observed of BS on the LPS-induced secretion of IL-6 was 0.0625–0.125 mg/mL, ST at 0.25–0.5 mg/mL. (Fig. 2) Furthermore, BS and ST suppressed the LPS-induced expression of caspase-1 gene in dose-dependent manner. (Fig. 3–4) Caspase-1 is a cysteine protease that converts the inactive form of IL-1β to the active inflammatory cytokine. Conclusions: Our preliminary study showed that AMPK activators, BS and ST, reduced LPS-induced inflammation in macrophages by combined inhibition of IL-6 secretion and block of inflammatory gene caspase-1 expression in RAW264.7 macrophage cell line. This result implicates anti-inflammatory effect of BS and ST, which may be induced by activation of AMPK and then regulated via NLRP3 pathway and caspase-1 expression. Funding Sources: This study is supported by the research funding from Shanghai Anti-Aging Research Center, Nu Skin Enterprises, Shanghai, China. Supporting Tables, Images and/or Graphs: